Recent Advances in Complex Functional Materials From Design to Application - Longo, Elson; La Porta, Felipe de Almeida; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book we explore new approaches to understanding the physical and chemical properties of emergent complex functional materials, revealing a close relationship between their structures and properties at the molecular level. The primary focus of this book is on the ability to synthesize materials with a controlled chemical composition, a crystallographic structure, and a well-defined morphology. Special attention is also given to the interplay of theory, simulation and experimental results, in order to interconnect theoretical knowledge and experimental approaches, which can reveal new scientific and technological directions in several fields, expanding the versatility to yield a variety of new complex materials with desirable applications and functions. Some of the challenges and opportunities in this field are also discussed, targeting the development of new emergent complex functional materials with tailored properties to solve problems related to renewable energy, health, and environmental sustainability. A more fundamental understanding of the physical and chemical properties of new emergent complex functional materials is essential to achieving more substantial progress in a number of technological fields. With this goal in mind, the editors invited acknowledged specialists to contribute chapters covering a broad range of disciplines. .
Part I - Advances in the processing of complex functional materials -- Multifunctional complex oxides processing -- Carbothermal Reduction Synthesis: An alternative approach to obtain single-crystalline metal oxide nanostructures -- Modification of complex materials using a pressure-assisted heat treatment -- Preparation of polymeric mats through electrospinning for technological uses -- Part II - Probing the functionality and applications of novel complex functional materials -- Morphology and optical properties of SrWO4 crystals synthesized by the co-precipitation and polymeric precursor methods -- Optical properties of semiconductor nanocrystals into the glass and colloidal system -- X-ray excited optical luminescence -- Piezoelectric composites: Fabrication, characterization and application as sensor -- Functional nanomaterials for applications in energy conversion and storage -- Electrochemistry: a powerful tool for preparing semiconductor materials useful in decontamination of organic and inorganic pollutants, disinfection and CO2 reduction -- Nanostructured functional materials: Silver nanoparticles in polymer for the generation of antimicrobial characteristics -- Filled Carbon Nanotubes -- Characterization of nanocarbons: graphene and graphene nanoribbons -- Design and applications of metal-organic framework -- Part III - Computational perspectives in complex functional materials -- Review on simulation models for materials and biomolecular study and design -- Iron oxides applied to catalysis -- Bridging Structure, Reactivity and Real-Space Topology: Understanding Electron Flow, Molecular Mechanism and Material Behaviour.
Keywords: Nanotechnology; Physical chemistry; Condensed matter; Nanotechnology; Physical Chemistry; Condensed Matter Physics